Salvianolic acid B attenuates inflammation and prevent pathologic fibrosis by inhibiting CD36-mediated activation of the PI3K-Akt signaling pathway in frozen shoulder - Yan, Yan; Zhou, Min; Meng, Ke; Zhou, Chuanhai; Jia, Xiaoyu; Li, Xinhao; Cui, Dedong; Yu, Menglei; Tang, Yiyong; Li, Ming; Zhang, Jinming; Wang, Zhuo; et al. (Frontiers in Pharmacology, 2023)
Frozen shoulder (FS) is characterized by pain and limited range of motion (ROM).Inflammation and fibrosis are accepted as main pathologic processes associated with the development of FS. However, the intrinsic mechanisms underlying pathologic fibrosis remain unclear. We aimed to elucidate the key molecules involved in pathologic fibrosis and explore new therapeutic targets for FS. Synovial fibroblasts isolated from patient biopsies were identified using immunofluorescence. Western blotting, RT-qPCR, cell adhesion tests, and would-healing assays were used to evaluate the fibrosis-related functions of synovial fibroblasts. Elevated cluster of differentiation 36 (CD36) expression was detected in FS using western blotting and immunohistochemistry. Salvianolic acid b (SaB) inhibited CD36, blocking synovial fibroblast-induced inflammation and fibrosis. Our RNA-seq data showed that knocking down CD36 dramatically impaired the capacity of synovial fibroblasts for cell adhesion and that the PI3K-Akt signaling pathway may be crucial to the fibrotic process of FS. By up-regulating CD36 and inhibiting the phosphorylation of Akt, we demonstrated that CD36 promotes pathologic fibrosis by activating the PI3k-Akt pathway. Finally, rats treated with SaB had improved ROM and less collagen fiber deposition than the FS model group.Conclusions: SaB attenuates inflammation and inhibited the CD36-mediated activation of the PI3K-Akt signaling pathway to block pathologic fibrosis of FS in in vitro and in vivo models.